(untitled) (Journal of Partial Differential Equations, 1990)
In practical problems there appears higher-order equations of changing type([1]). But, there are only a few of papers concerning this type of equations ([2]-[6]). In this paper, the global existence of regular solutions to the Initial-boundary value problem for a class of higher-order system of equations of changing type with a strong nonlinear term is studied.